PELATIHAN PEMBUATAN ABON IKAN DARI HASIL NELAYAN SEBAGAI INOVATIF GUNA MENINGKATKAN EKONOMI MASYARAKAT DESA SELENGEN KECAMATAN KAYANGAN - Firmansyah, Firmansyah; Aini, Rohmiatun; Yunia, Indra; Chatami, Lalu Radinal Ihya; Fitriani, Baiq Annisa; Nisa, Haerun; Supasta, I Gede; Hartati, Junia; Babgi, Faiz Karim (Universitas Mataram, 2023)
Sea fish is one of the problems in the utilization of natural resource commodities in Selengen Village. In addition, the limited knowledge and skills of the community to innovate in fish processing, especially Layang fish, which is useful for improving the people's economy in Selengen Village. Processed fish will be made into a food product that can attract public interest. The overall form of activity includes: Socialization and training on the production of shredded fish from the type of Layang fish, Production of shredded Layang fish, Marketing of the shredded Layang fish production to the market. The Layang shredded fish production activity is a continuation of the program mentioned above. This program is carried out for the utilization of Layang fish to be processed into shredded Layang fish. It is hoped that by carrying out this marketing, PKK mothers can re-practice the results of the training that has been taught and prepare for independence to produce shredded fish on their own to add to the economy. It is hoped that in the future the women in Selegen village will know better how to make shredded meat with the right dosage, various flavors and attractive packaging. Because in Selengen village there are no MSMEs yet, it is suggested that the village can revive BUMDES and form MSMEs so that the potential in the village can be disseminated and can help the community's economy.